A Deterministic Parallel Computing Approach Optimised for Multicore Architecture - Iqbal, Shahid (International Journal of Computer Sciences and Engineering, 2015)
In software computing, computation is done either deterministic or non-deterministic approach. Deterministic approach includes the constraint like dependency of data in which no random computation is involved. This paper talks about how to achieve more parallelism in context of a deterministic computation approach for the dual-core architecture. In this paper a new Scheduling algorithm which termed as “LA Scheduling” algorithm and its associated component has been presented which is mainly optimised for dual core architecture. Simulation result shows that it helps in reducing the response time of a program and average speedup has been increased